Visual acuity increases up to 7 years after Descemet Stripping Automated Endothelial Keratoplasty - Hansen, M.S.; Correll, M.H.; Julian, H. (Acta ophthalmologica (Oxford, England), 2015)
Purpose Descemet Stripping Automated Endothelial Keratoplasty (DSAEK) for corneal endothelial dysfunction restores vision up to 5 years post‐surgery, yet outcome exceeding this time span remains unknown. This study reports outcomes up to 7.8 years post‐DSAEK in a prospective observational study. Methods The cohort consists of the first 30 consecutive DSAEK‐surgeries in 25 subjects at Rigshospitalet Copenhagen, in 2006–2007. Data are reported for 14 eyes of 10 subjects (median age 65.8 years, range 55–79 years) who completed more than 5 years of follow‐up (mean 6.8 years, range 5.6–7.8). Best spectacle‐corrected visual acuity (BSCVA) was obtained using Snellen charts and transformed to logMAR. Endothelial cell density (ECD) was calculated by a digital Topcon SP‐3000P specular microscope camera. Central corneal thickness (CCT) was measured by OCULUS Pentacam. Results BSCVA improved from −0.54 ± 0.17 logMAR (mean ± SD; Snellen equivalent 6/18) pre‐DSAEK to −0.29 ± 0.32 logMAR (6/12) at 1 year (mean 1 year, range 0.6–1.4 years) and further improved to −0.17 ± 0.09 logMAR (6/9) at 7 years (mean 6.8, range 5.6–7.8 years). The proportion of eyes with BSCVA better than Snellen 6/12 was 64% at 1 year and 93% at 7 years. All grafts had ECD above 2000 cells/mm2 pre‐DSAEK. ECD decreased in most grafts from 1 to 7 years (mean loss 31%, range 10–43%), yet 5 grafts showed increased ECD (mean gain 39%, range 6–81%). CCT remained unchanged from 1 to 7 years post‐DSAEK (p = 0.39). 16 of the initial 30 eyes were lost to follow‐up due to death (8 eyes), graft failure (3 eyes), or other circumstances (5 eyes). Conclusions DSAEK provides continuous improvement of visual acuity up to 7.8 years post‐surgery with stable corneal thickness, and decreasing endothelial cell density in most grafts, yet some grafts showed surprising increase.